The First Protocol for Assessing Welfare of Camels - Padalino, Barbara; Menchetti, Laura (Frontiers in Veterinary Science, 2021)
This study aimed at developing and describing a protocol for assessing welfare in camels. A literature review was conducted searching for scientific papers on assessment of animal welfare, and camel behavior, management, physiology, and pathology. The paradigms of Five Freedoms, the Five Domains Model, and the welfare principles and criteria applied by the Welfare Quality® and AWIN methods were then adapted to camels. A combination of animal-, resource- and management-based indicators were selected and categorized according to three levels of assessment: i) Caretaker, ii) Herd, and iii) Animal. The Caretaker level is an interview of 23 questions exploring the caretaker’s background, experience, and routine management practices. The Herd level is a check of the herd and of the place (i.e. box/pen) where camels are kept. The Animal level is a visual inspection aiming at evaluating individual camel behavior and health status. The selected indicators are presented for each welfare principle and level; for instance for the principle of “Appropriate nutrition”, feeding management is investigated at Caretaker level; feed availability and quality, the number of feeding points, and camel feeding behavior are recorded at Herd level, while BCS is evaluated at Animal level. In this study, recording sheets for the assessment at the three levels were presented and how to conduct the assessment was described and discussed. Further applications of the proposed tool for assessing camel welfare on an elevated number of farms are needed to validate the presented indicators as well as the thresholds for their acceptability and to develop welfare standards in camels